Removal of microplastics via drinking water treatment: Current knowledge and future directions. (July 2020) - Shen, Maocai; Song, Biao; Zhu, Yuan; Zeng, Guangming; Zhang, Yaxin; Yang, Yuanyuan; Wen, Xiaofeng; Chen, Ming; Yi, Huan
Abstract: The occurrence of microplastics in drinking water systems has increasingly become a major environmental challenge. Although the potential impacts of microplastics in drinking water on humans are not yet fully understood, microplastics attract the public health concern when they are consumed by humans through drinking water systems. Current drinking water treatment plants constitute an obstacle to the entry of microplastics from raw water into daily drinking water. Therefore, understanding the behaviors of drinking water treatment process and the fates of microplastics in drinking water treatment plants are very important. We systematically reviewed the available knowledge on the global existence of microplastics in raw water, treated water and tap water in this paper. This will offer a new perspective for the threat of microplastics in drinking water to human health and help to formulate effective strategies for microplastic monitoring. The existing knowledge of microplastic removal by different treatment processes was also thoroughly discussed. Additionally, the potential challenges of microplastic removal from treatment processes and remediation strategies of microplastics in drinking water were also put forward. The relationship between the properties and behavior of microplastics during different treatment processes is suggested to explore in the future. Graphical abstract: Image 1 Highlights: Microplastics (MPs) may pose threats to human health through drinking water. MPs have been found in raw water and drinking water (tap and bottled water). DWTPs are important barriers for MPs to enter human body. The characteristics of DWTPs to remove MPs should be fully understood. The pollution of MPs in aquatic environment should also be concerned and stopped.